Validation of a skinfold based index for tracking proportional changes in lean mass. Issue 3 (27th February 2006) - Slater, G J; Duthie, G M; Pyne, D B; Hopkins, W G
Abstract : Background: The lean mass index (LMI) is a new empirical measure that tracks within-subject proportional changes in body mass adjusted for changes in skinfold thickness. Objective: To compare the ability of the LMI and other skinfold derived measures of lean mass to monitor changes in lean mass. Methods: 20 elite rugby union players undertook full anthropometric profiles on two occasions 10 weeks apart to calculate the LMI and five skinfold based measures of lean mass. Hydrodensitometry, deuterium dilution, and dual energy x ray absorptiometry provided a criterion choice, four compartment (4C) measure of lean mass for validation purposes. Regression based measures of validity, derived for within-subject proportional changes through log transformation, included correlation coefficients and standard errors of the estimate. Results: The correlation between change scores for the LMI and 4C lean mass was moderate (0.37, 90% confidence interval −0.01 to 0.66) and similar to the correlations for the other practical measures of lean mass (range 0.26 to 0.42). Standard errors of the estimate for the practical measures were in the range of 2.8–2.9%. The LMI correctly identified the direction of change in 4C lean mass for 14 of the 20 athletes, compared with 11 to 13 for the other practical measures of lean mass. Conclusions: The LMI is probably as good as other skinfold based measures for tracking lean mass and is theoretically more appropriate. Given the impracticality of the 4C criterion measure for routine field use, the LMI may offer a convenient alternative for monitoring physique changes, provided its utility is established under various conditions.